Impact of Five Succinate Dehydrogenase Inhibitors on DON Biosynthesis of Fusarium asiaticum, Causing Fusarium Head Blight in Wheat - Xu, Chao (Toxins (Basel), 2019)
Deoxynivalenol (DON) is a class of mycotoxin produced in cereal crops infected with Fusarium graminearum species complex (FGSC). In China, FGSC mainly includes Fusarium asiaticum and F. graminearum. DON belongs to the trichothecenes and poses a serious threat to the safety and health of humans and animals. Succinate dehydrogenase inhibitors (SDHIs) are a class of fungicides that act on succinate dehydrogenase and inhibit the respiration of pathogenic fungi. In this study, the fungicidal activities of five SDHIs, including fluopyram, flutolanil, boscalid, benzovindiflupyr, and fluxapyroxad, against FGSC were determined based on mycelial growth and spore germination inhibition methods. The five SDHIs exhibited better inhibitory activities in spore germination than mycelial growth. Fluopyram exhibited a higher inhibitory effect in mycelial growth and spore germination in comparison to the other four SDHIs. In addition, the biological characteristics of F. asiaticum as affected by the five SDHIs were determined. We found that these five SDHIs decreased DON, pyruvic acid and acetyl-CoA production, isocitrate dehydrogenase mitochondrial (ICDHm) and SDH activities, and NADH and ATP content of F. asiaticum but increased the citric acid content. In addition, TRI5 gene expression was inhibited, and the formation of toxisomes was disrupted by the five SDHIs, further confirming that SDHIs can decrease DON biosynthesis of F. asiaticum. Thus, we concluded that SDHIs may decrease DON biosynthesis of F. asiaticum by inhibiting glycolysis and the tricarboxylic acid (TCA) cycle. Overall, the findings from the study will provide important references for managing Fusarium head blight (FHB) caused by FGSC and reducing DON contamination in F. asiaticum-infected wheat grains.